PENGARUH MODEL PEMBELAJARAN KOOPERATIF PICTURE AND PICTURE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA DI KELAS III DI MI TARBIYATUSSHIBYAN - Mumun Munawaroh; Rofi'ah Rofi'ah (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2018)
The purpose of this study is to determine the improvement of student learning outcomes by using cooperative learning model picture and picture on i class III subjects, to apply cooperative learning model picture and picture on science class III subjects, to know the effect of cooperative learning model picture and picture to the results of learning 3rd grade MI Tarbiyatusshibyan. This research uses quantitative research that is quasi experiment and pre experimental design and post test control group. the population observed in the study were students and MI Tarbiyatusshibyan students, by taking sample of class III A with the number of students as many as 20 people as experimental class and class III B with the number of students as many as 18 people as control class. the result of the research shows that there is a significant effect of the learning result of the science students between the experimental class and the model of cooperative learning picture and picture and control class with conventional learning in the form of lecture method. it is proved from the t-test at a significant level of 5% of 2.03 while a significant level of 1% of 2.72 and t results of 4.685 this means that t arithmetic is greater than t table then it can be written 2.03 < 4.685 > 2.72 then alternative Hypothesis (Ha) is accepted and Hypothesis zero (Ho) is rejected.